Spiralothelphusa gibberosa, a new freshwater crab (Brachyura: Gecarcinucidae) from Thrissur district, Kerala, India - Pati, S.k.; Devi, A.r. Sudha (Zootaxa, 2015)
A new species of freshwater crab, Spiralothelphusa gibberosa n. sp. is described from rice fields near Kizhoor in Thrissur district of Kerala in southern India. The new species is easily differentiated from its congeners by its first male pleopod (G1), which has a long, less strongly twisted terminal segment and distal portion of subterminal segment in addition to a setose hump on the outer margin of the non-twisted portion. Key to the species of the genus Spiralothelphusa Bott, 1968, is provided. We recognized S. wuellerstorfi (Heller, 1862), as a new record to Maharashtra based on specimens wrongly identified as S. hydrodroma (Herbst, 1794), by Pati & Sharma (2014).